The life and work of Antonio Maria Valsalva (1666–1723) – Popping ears and tingling tongues. (May 2018) - Jacobs, Nathan; Bossy, Michele; Patel, Amish
The Valsalva manoeuvre is the increase in intra-thoracic pressure achieved by attempted expiration against a closed upper airway. The contraction of abdominal and other accessory muscles of respiration attempt to decrease the intra-thoracic volume, whilst the airway is closed either by the forceful apposition of the vocal cords or else by firmly closing the lips and sealing off the nose (e.g. by pinching it). Valsalva described this manoeuver as a way of checking the patency of the Eustachian tube. However, it has found other uses, including as a way to terminate episodes of supraventricular tachycardia and stopping ear popping-pain on high altitude flights. But who was Valsalva?